Reverse Shoulder Arthroplasty, Deltopectoral Approach vs. Anterosuperior Approach: An Overview of the Literature - Paraskevas Georgoulas (Frontiers Media S.A., 2021)
Reverse shoulder arthroplasty (RSA) has become an optimal treatment for numerous orthopedic entities, such as rotator cuff tear arthropathies, pseudoparalysis, fracture sequelae, acute fractures, failed arthroplasties, osteoarthritis, and rheumatoid arthritis, and is linked with relief of topical pain and regaining of functionality. Presently, RSA has been conducted through anterosuperior (AS) or deltopectoral (DP) approach. The aim of the study was to discuss both approaches and to examine broadly their features to render a comparison in terms of clinical effectiveness. An electronic search in PubMed, EMBASE, and Google Scholar databases was performed, using combinations of the following keywords: RSA, DP approach, AS approach, notching, and cuff tear arthropathy. A total of 61 studies were found, and 16 relevant articles were eventually included. Currently published literature has not shown significant diversities in the clinical course due to approach preference; risk of instability seems to be greater in DP approach, while regarding scapular notching and fracture rates the findings were conflicted. In addition, the AS approach has been associated with decreased risk of acromial and scapular spine fractures. In conclusion, both surgical approaches have shown similar clinical outcomes and effectiveness concerning pain and restoring range of motion (ROM) in rotator cuff tear arthropathies. In the future, further investigations based on large-scale well-designed studies are required to address clinical gaps allowing in-depth comparison of both approaches.